Applying English proficiency test using Google Form and Zoom - Norita Prasetya Wardhani; Satrio Priyo Anggoro; Hardono Hardono (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2022)
English proficiency tests are one of the requirements for graduation on many campuses in Indonesia. The scores of these tests can also be used for job applications. Tests can be conducted both offline (paper-based) and online (internet-based), with the latter allowing participants to take the test from any location. Online tests require a laptop with a webcam, mouse, headset, and phone. This study used Google Form and Zoom Cloud Meeting as the test platforms, and qualitative research methods were used to understand the benefits, obstacles, and problems that arose. Data was collected through investigation, questionnaires, and interviews, and the researcher recorded everything that happened during the study. Some benefits, obstacles, and problems were found when using Google Form and Zoom Cloud Meeting. Keywords: English proficiency test; internet-based test; Zoom Cloud Meeting,; Google Form